Whither economics? - Dyck, Robert G. (Naše gospodarstvo, 2011)
This paper provides an overview of the failure of market-based economics and offers a checklist for change, starting with a revised scientific approach based on complexity, fractal geometry, and systems theory. The paper argues that rationality is defined as much-if not more than-by caring and collaboration as by self-interest. It also argues for greater economic democracy, community based-entrepreneurship, scale neutrality, and greater adaptive resilience to perturbations. In conclusion, the paper urges a cautious but persistent approach to the problem of cultural adaptation to a changed system.
Keywords: democracy; demokracija; podjetništvo; tržno gospodarstvo; podjetja; družbena odgovornost; ekonomske teorije